Lewis Acid Catalyzed [3+2] Coupling of Quinone Monoacetals or Quinone Imine Ketals with Vinylcarbamates - Liao, Li-Hua; Zhang, Min-Min; Liao, Yi-Jun; Yuan, Wei-Cheng; Zhang, Xiao-Mei (Synlett, 2015)
A mild and concise [3+2] coupling of quinone monoacetals or quinone imine ketals with vinylcarbamates promoted by Lewis acid was realized. Various 2-carbamate-2,3-dihydrobenzofurans and 2-carbamate-indolines have been prepared in moderate to good yields.
Keywords: [3+2] coupling; Lewis acid; synthesis; 2-carbamate-2,3-dihydrobenzofurans; 2-carbamate-indolines